Akad Pernikahan Melalui Zoom dalam Perspektif Fikih - Hamdani, Muhammad; Masykur, Muhammad Riduwan; Hamidah, Tutik (Fakultas Syariah INSURI Ponorogo, 2023)
The modern era is greatly facilitated by using technology. This is a shortcut to take advantage of technology, one of which is reducing distance and time facilitating communication between people without meeting each other. So that it becomes a new innovation in terms of marriage through Zion technology which makes it easier for the bride and groom who don't have to be in the same place. lighten the burden on the bride and groom in traveling expenses. But this raises questions as well as the views of various scholars and groups, because there was no law in ancient times. The purpose of this study is to find out the law of marriage contracts through zoom in the view of the scholars. The method used in this study uses the Library Research method and literature that is aligned with the theme. The results of this study are that, according to the Hanafi school of thought, online marriage is permissible because it is confirmed by the Prophet's Hadith that the Prophet SAW once performed a marriage using a piece of paper and in a different place between the bride and groom, supported by the MUI fatwa. However, according to the view of the Syafii school of thought, this is not permissible because the bride and groom must be in the same place.